National culture and management control systems: an explanatory study on the implementations of foreign MCS in Japan / Wooseok Suh - Suh, Wooseok (Faculty of Accountancy, 2014)
In a borderless international economy, the relationship between national culture and Management Control Systems (MCS) is inseparable and complex. A multinational corporation faces cultural differences across countries in operating and controlling its subsidiary. And, the differences in cultures influence the implementation of organization’s strategies that is characterized as MCS. This study reports two different cases of MCS implementations in a Japanese organization by foreign-owned multinational corporations. The changes of MCS implementation and its interaction with Japanese employees have been observed with American company’s acquisition of a French-Japanese joint-venture. Through the changes, Japanese employees experienced both goal congruence and anxiety between Japanese cultural context and foreign MCS. This paper deliberates the historical events from the perspective of national culture and MCS. Findings provide suggestions for potential directions of future cultural research in MCS.